Health, Nutrition, and Population in Madagascar 2000-09 - Sharp, Maryanne (World Bank, 2012)
With an income per capita US$400 in 2008, Madagascar is one of the poorest countries in the world. Poverty is widespread but with significant urban-rural differences (52 percent versus 74 percent). Health, nutrition, and the fight against communicable diseases and HIV/AIDS are key goals of the country's poverty reduction strategy, the Madagascar Action Plan 2007-2012. The National Health Sector and Social Protection Development Plan 2007-2011 was developed to strengthen the health system and improve service delivery to reduce neonatal, child and maternal mortality, address malnutrition and control communicable illnesses. The health sector has benefited from increasing investment over the last years, and a number of studies and surveys have been carried out, providing a wealth of information that is yet to be analyzed in a complementary way. This Country Status Report (CSR) seeks to capitalize on all of the existing data in the health sector, compare Madagascar to countries of similar income levels and assess the results achieved by the health system. The CSR provides an analysis of the population's health and nutrition status by linking health outcomes, household/individual behaviors, community factors, government interventions, and service provision. Although Madagascar is performing beer than the SSA average of 645 per 100,000 live births, the maternal mortality rate has stagnated over the last decade and in 2008/09 was estimated at 498. Health care seeking behavior for preventive child health services at the health facility level is improving. Complete immunization coverage stands at 62 percent in 2008 (for children 12 to 23 months), but there are still large differences in coverage across regions, place of residence, and income groups.